Teacher Performance Evaluation Based on Holistic Approach to Improve Education Quality at SMP Muhammadiyah 57 - Nasution, Syarifuddin; Siahaan, Amiruddin; Khairuddin, Khairuddin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Evaluation is the initial process for planning the way forward. Still, in practice, it was found that most teacher performance evaluation programs did not positively impact improving the quality of education. This study describes the strategic planning, organisational structure and implementation outcomes of the teacher performance evaluation programme at SMP Muhammadiyah 57 Medan. Data were collected using interviews, observation, and document analysis and validated by triangulation using a qualitative descriptive approach. Strategic planning, supported by specific objectives, standardised procedures, and professional development efforts, emerged as the main approach to the program's success, according to the findings. This high-level assessment combined national policy objectives with a region-specific approach, blending theoretical models with realities on the ground. An organisational model detailed how systematic implementation was carried out, assigning responsibilities to evaluators and administrators. However, limited teacher involvement in developing evaluation instruments and unclear communication of results were identified as remaining problems, resulting in dissatisfaction and mismatched expectations. This study highlights the importance of collaborative planning, transparent feedback mechanisms and evaluator training to build trust and improve program effectiveness. The study provides a comprehensive model of teacher assessment through self-evaluation, motivational incentives and strong regulation, which allows for practical applications to support educational institutions in improving assessment processes and enhancing teaching quality